2007
DOI: 10.1002/chem.200601416
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Crystalline and Electron‐Deficient Coronene Oligocarboxylic Esters and Imides By Twofold Benzogenic Diels–Alder Reactions on Perylenes

Abstract: Alkyl esters, imides and imido-esters of coronene-tri-, -tetra- and -octacarboxylic acids are accessible by a twofold oxidative benzogenic Diels-Alder reaction. Alkyl acrylates add to perylene, and maleic alkyl imides react twice with perylene as well as with perylene-tetracarboxylic tetraesters. Coronenes substituted with a greatly variable number of electron-withdrawing substituents are thus accessible, and di- and tetraimide derivatives are shown to be very pronounced electron-acceptor materials. The tri- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 30 publications
1
79
0
2
Order By: Relevance
“…We have recently shown that up to four alkylimide substituents can be introduced into coronene, [13] Langhals and co-workers have described triimide derivatives of benzoA C H T U N G T R E N N U N G [ghi]perylene [14] and tri-and tetraimide derivatives of benzannelated terrylenes, [15] and laterally condensed dimers and trimers of perylene-diimides have been described by Wang and co-workers. [16] None of these tri-or tetraimide materials have been reported to show columnar liquid-crystalline self-assembly under ambient conditions.…”
Section: Introductionmentioning
confidence: 95%
“…We have recently shown that up to four alkylimide substituents can be introduced into coronene, [13] Langhals and co-workers have described triimide derivatives of benzoA C H T U N G T R E N N U N G [ghi]perylene [14] and tri-and tetraimide derivatives of benzannelated terrylenes, [15] and laterally condensed dimers and trimers of perylene-diimides have been described by Wang and co-workers. [16] None of these tri-or tetraimide materials have been reported to show columnar liquid-crystalline self-assembly under ambient conditions.…”
Section: Introductionmentioning
confidence: 95%
“…The π‐extended PAH 1 displayed distinct absorption spectral features with remarkably high molar absorptivities in the visible range (Figure 3). Similar to other two‐dimensional PAH scaffolds, such as pyrenes,28 coronenes,13a or hexabenzocoronenes,29 the absorption spectrum of 1 is not dominated anymore by the lowest‐energy S 0 –S 1 transition ( λ max =584 nm, ɛ max =141 200  m −1  cm −1 ) but by a higher‐energy absorption band at λ max =489 nm, which is characterized by well‐resolved vibronic progressions and a very high molar extinction coefficient of 278 300  m −1  cm −1 . According to TD‐DFT calculations, the transition dipole moments of these two main transitions are aligned along the short and long molecular axes of the central pyrene core (Figure 3, right).…”
mentioning
confidence: 99%
“…Functionalized coronenes are, however, very rare. [12,13] To tune the electronic properties and intermolecular order, a versatile synthetic method is required to introduce substituents and control the symmetry of coronenes. This helps to match up the energetic levels of coronene with those of electrode materials, as needed for organic electronics.…”
mentioning
confidence: 99%